Раціональні умови фракційної кристалізації соняшникової олії пальмітинового типу із розчину - Куниця, Катерина Вікторівна; Литвиненко, Олена Анатоліївна; Гладкий, Федір Федорович (Технологический центр, 2014)
Стаття присвячена визначенню раціональних умов фракціювання соняшникової олії пальмітинового типу із розчину. Наведено обґрунтування вибору розчинника для процесу фракційної кристалізації. Отримано дані щодо виходу цільової фракції та її температури плавлення в залежності від основних параметрів процесу, а саме: темпу охолодження та концентрації олії в розчиннику.

The paper deals with the definition of rational conditions for fractionation of sunflower oil of palmitic type from solution. Justification of solvent selection for the fractional crystallization process is given. The work is aimed at the definition of rational fractionation conditions and obtaining dependences of target fraction output and its melting point on the key process parameters, such as process temperature and oil concentration when applying new solvent. The data on the dependences of target fraction output and its melting point on the key process parameters, namely, temperature and oil concentration in solvent was obtained. As a result of the studies it was found that using the new solvent, namely butyl alcohol is effective for the fractional crystallization process. Total process duration, depending on the oil amount in the solution is 12-24 hours. When using butyl alcohol, there is crystallization acceleration by 4.3 times: from 68 hours without solvent up to 16 hours for 40-60 % oil solutions in solvent. Fractionation from butyl alcohol leads to oil crystallization acceleration, lower capture of the liquid fraction, and provides achieving higher melting points of high-melting fraction as compared to fractionation from melt.
Rational conditions fractional crystallization of sunflower oil palmitic type from solution
Keywords: бутиловий спирт; молекулярна взаємодія; рицинолева кислота; розчинність жирів; sunflower oil of palmitic type; fractional crystallization; butyl alcohol; solution